Social resource as a critical and overlooked factor for patient safety in low-resource settings - Hilary Edgcombe; Gatwiri Murithi; Mary Mungai; Stephen Okelo; Sassy Molyneux; Helen Higham; Mike English (Frontiers in Health Services, 2025)
Clinicians, NGOs, funders and academics (among others) in global health are accustomed to discussion of the “low-resource setting”. Commonly, the resources implicit in this term are physical (equipment, drugs) and infrastructural (electricity, water and sanitation) in nature. Human resources are well recognised as scarce in this context too, and the focus in most “workforce” research is on the number, distribution and/or training of healthcare workers. In this article, we make the case for closer examination of “social resource” as necessary to patient safety and distinct from simple enumeration of available/trained personnel. We use the clinical specialty of anaesthesia as a case study, identifying the different ways in which social resource is necessary to enable safe practice for anaesthesia providers, and the potential challenges to accessing social resource relevant in the low- and middle-income context. Finally, we suggest ways in which social resource for anaesthesia professionals in LMICs might be meaningfully investigated, with a view to improving its priority and access for safe anaesthesia care worldwide.